The growth and yield of soybean varieties on differences light - FAHROZI FAHROZI; Lisa Mawarni; Chairani Hanum (Jurnal Agroekoteknologi, 2018)
Increased soybean yields have a meaning in the food industry. The expansion of planting area is one of extensification effort of soybean. Soybean planted on palm oil productive interrow is an alternative to increasing productivity. Soybean responsed plants to light low is the changed in morphology and yield. The objective of the research was to studied growth and yield of soybean varieties on differences light intensity. This research used Factorial Split Plot Design with 3 replications. The main plot were: differences light intensity 30% and 50% and sub plot were: 4 soybean varieties (Grobogan, Anjasmoro, Dena 1, Wilis). This research conducted Deli Serdang district, North Sumatera. The effect of treatment differenes light intensity was not significant on plant height, stem diameter, leaf area index, productive brances, and dry weight of seed. Each of the varieties gave different responses to the plant height and productive branches. The differences light intensity treatment on the variety will increase the leaf area index  in line with the decrease in light intensity except on the grobogan varieties.   Keyword: Oil palm shading, soybean varieties.